Colorimetric Reverse Transcription Loop-Mediated Isothermal Amplification with Xylenol Orange Targeting Nucleocapsid Gene for Detection of Feline Coronavirus Infection - Kotchaporn Khumtong; Witsanu Rapichai; Wichayet Saejung; Piyamat Khamsingnok; Nianrawan Meecharoen; Siriluk Ratanabunyong; Hieu Van Dong; Supansa Tuanthap; Amonpun Rattanasrisomporn; Kiattawee Choowongkomon; Oumaporn Rungsuriyawiboon; Jatuporn Rattanasrisomporn (Viruses)
Feline infectious peritonitis (FIP), a devastating disease with near-complete mortality, is caused by the feline coronavirus (FCoV) and affects domestic cats worldwide. Herein, we report the development of a reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay incorporating xylenol orange (XO) as a visual indicator for FCoV detection. The assay employed six oligonucleotide primers targeting regions of the nucleocapsid (N) gene. Under optimized conditions (65 °C, 60 min), amplification products were detected through pH-dependent colour changes in the XO dye. The RT-LAMP-XO assay exhibited high specificity for FCoV, with no cross-reactivity against other common feline viral pathogens. While the detection limit (1.7 × 101 copies/µL) was an order of magnitude higher than that of qPCR, the method offered advantages in simplicity and speed compared to existing diagnostic approaches. Although less sensitive than qPCR, the RT-LAMP-XO assay may serve as a rapid screening tool when used in combination with additional primer sets. These findings demonstrate the potential utility of XO-based RT-LAMP as a simple, visual detection method for FCoV infection.